2012
DOI: 10.1262/jrd.11-121h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of RNA Interference of BID and BAX mRNAs on Apoptosis in Granulosa Cell-derived KGN Cells

Abstract: Abstract. In mitochondrion-dependent type II apoptosis, BH3-interacting domain death agonist (BID) and BCL-2-associated X protein (BAX) promote death ligand and receptor-mediated cell death. In porcine ovaries, the levels of BID and BAX increase in follicular granulosa cells during atresia. In the present study, to confirm the pro-apoptotic activity of BID and BAX in granulosa cells, we examined the effect of RNA interference of BID or BAX on apoptosis using a human ovarian granulosa tumor cell line, KGN. By r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Moreover, this study showed that 3NP induced the release of cytochrome c , and the activation of caspase-3 was significantly attenuated after knockdown of BAX with siRNA ( Figure 5c and Figure 6c ), suggesting that DRAM1-dependent BAX upregulation is involved in 3NP-induced mitochondrial apoptotic pathway. To confirm if BID cleavage contributes to 3NP-induced apoptosis, BID siRNAs, which have been previously validated, 31 were used to silence BID ( Figure 6d ). The data showed that 3NP-induced caspase-3 activation was partially inhibited by BID siRNA ( Figure 6e ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this study showed that 3NP induced the release of cytochrome c , and the activation of caspase-3 was significantly attenuated after knockdown of BAX with siRNA ( Figure 5c and Figure 6c ), suggesting that DRAM1-dependent BAX upregulation is involved in 3NP-induced mitochondrial apoptotic pathway. To confirm if BID cleavage contributes to 3NP-induced apoptosis, BID siRNAs, which have been previously validated, 31 were used to silence BID ( Figure 6d ). The data showed that 3NP-induced caspase-3 activation was partially inhibited by BID siRNA ( Figure 6e ).…”
Section: Resultsmentioning
confidence: 99%
“…The BAX/BCL2 and BCLXs/BCLXl proapoptotic ratios were increased when Notch activation was inhibited, demonstrating an impaired function of mitochondria in these cells and the participation of the intrinsic apoptotic pathway in DAPT-induced apoptosis in KGN cells. The proapoptotic activity of BH3-interacting domain death agonist (BID) and BAX proteins has been recently confirmed in KGN cells by using the siRNA technique [47]. BAX expression has also been associated with apoptosis in ovarian cancer tissue, and patients expressing high levels of BAX in tumors have a significantly longer median survival than patients with low BAX expression [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…More than 99% of the growing follicles in the ovary are destined for atresia, which is usually first evident by apoptosis of the granulosa cells. Notably, BID expression increases during follicular atresia in the porcine ovary and knockdown of BID expression in human granulosa cell-derived KGN cells can suppress apoptosis (Sai et al 2011(Sai et al , 2012, suggesting a role for BID in regulating the normal process of follicular atresia. In addition to this natural process, BID may also be responsible for triggering follicular atresia following exposure to exogenous environmental toxicants such as di-n-butyl phthalate and the organochlorine pesticide methoxychlor, which are known to increase follicular atresia (Paulose et al 2012, Craig et al 2013.…”
Section: Bh3 Interacting Domain Death Agonistmentioning
confidence: 99%